The History of Moderate Islam in Indonesia and Its Influence on the Content of National Education - Inayatillah,; Kamaruddin,; M. Anzaikhan, (Journal of Al-Tamaddun, 2022)
Indonesia is a multicultural country consisting of various religions and ethnic groups. This diversity is unlikely to last long if the concept of Islamic teaching is filled with an exclusive and radical understandings. Moderate in Indonesia is known as religious moderation or Islam Wasathiyah which is understood as a concept of religious understanding that positions itself in the middle or has a middle stand. Moderate Islam in Indonesia came along with the teachings of Islam in the 13th century. According to historians, the content of Islam entering Indonesia has experienced moderation so that it is different from the Islamic teachings in Mecca and Egypt at that time. Yet, it is this difference that made Islam in Indonesia survived and turned to be the dominant religion in the archipelago. The history of moderate Islam in Indonesia begins with the Sufis in Aceh, followed by Walisongo in Java, public figures and Islamic organizations during the fight of independence, and authorities of the Ministry of Religious Affairs in the present days. This article is a result of a library research conducted in a qualitative approach. The method used for study is descriptive analysis toward recent relevant sources within the last 3 years. The result of study showed that the history of moderate Islam in Indonesia historically moves from essential dimension to authoritative one. The essential dimension covers moderate Islam in terms of Islam Wasathiyah (middle stand) values in various persuasive approaches. Whereas authoritative dimension is referred to the time moderate Islam is taken into the formal forms (government programs) called “Religious Moderation”. This further penetrates the content of education and feature of national curriculum.